2019
DOI: 10.1080/02763893.2018.1534180
|View full text |Cite
|
Sign up to set email alerts
|

Testing of the Function Focused Environment Assessment and the Function Focused Policy Assessment in Assisted Living

Abstract: This study tested two new instruments, the Function Focused Environment Assessment (FF-EA) and the Function Focused Policy Assessment (FF-PA). The measures were developed for clinical evaluation of AL settings to help optimize function and physical activity among residents. A total of 106 AL settings and 242 residents were included. There was evidence of item reliability (0.92) and interrater reliability (kappa=0.40, p=.015; percent agreement 85%) of FF-EA and item reliability (0.89) and interrater reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This study used baseline data collected by research assistants all of whom had prior experience working with this population. Descriptive information for the facility included size based on number of beds, profit status (for profit or not for profit) and an assessment of the environment and policies related to optimizing function and physical activity using the Function Focused Environment Assessment and Function Focused Policy Assessment in Assisted Living (Resnick, Galik, et al, 2019). Descriptive information for residents included age, gender, number of comorbidities, and race.…”
Section: Methodsmentioning
confidence: 99%
“…This study used baseline data collected by research assistants all of whom had prior experience working with this population. Descriptive information for the facility included size based on number of beds, profit status (for profit or not for profit) and an assessment of the environment and policies related to optimizing function and physical activity using the Function Focused Environment Assessment and Function Focused Policy Assessment in Assisted Living (Resnick, Galik, et al, 2019). Descriptive information for residents included age, gender, number of comorbidities, and race.…”
Section: Methodsmentioning
confidence: 99%
“…Champion and research nurse facilitator complete the Function Focused Environment Assessment and the Function Focused Policy Assessment in Assisted Living 22 …”
Section: Methodsmentioning
confidence: 99%
“…As shown in Table 2, FFC-AL-EIT is a four-step approach that is implemented by a research nurse facilitator working with a facility-identified champion and stakeholder team over a Champion and research nurse facilitator complete the Function Focused Environment Assessment and the Function Focused Policy Assessment in Assisted Living. 22 Research nurse facilitator reviews way to alter the environment and policies to optimize function and physical activity.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation